2022
DOI: 10.3390/jpm12122001
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Variants in COVID-19 Disease: A Focus on Disease Severity and Vaccine Immunity in Patients Admitted to the Emergency Department

Abstract: Tracking SARS-CoV-2 variants along with vaccinations are fundamental for severe COVID-19 disease prevention. A study was performed that focused on 43 patients with the SARS-CoV-2 infection who were admitted to the Emergency Department. RT-PCR–positive nasopharyngeal samples were sequenced using the MiSeq II system for variant detection. The main reason for Emergency Department admission was COVID-19 (67%), followed by other causes (33%); 51% patients were unvaccinated or vaccinated with a single dose and 49% h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…After the start of the general vaccination of COVID-19, most of the patients were hospitalized in the normal care department of Corona. The results of the study of M. Moffa et al (2022) [ 24 ] as well as the results of the study M. Fogolari et al (2022) [ 25 ] is in line with this finding of the present study. The results of their studies showed that after the start of general vaccination of COVID-19, most of the patients were hospitalized in the general care departments for corona patients.…”
Section: Discussionsupporting
confidence: 93%
“…After the start of the general vaccination of COVID-19, most of the patients were hospitalized in the normal care department of Corona. The results of the study of M. Moffa et al (2022) [ 24 ] as well as the results of the study M. Fogolari et al (2022) [ 25 ] is in line with this finding of the present study. The results of their studies showed that after the start of general vaccination of COVID-19, most of the patients were hospitalized in the general care departments for corona patients.…”
Section: Discussionsupporting
confidence: 93%